Security administrator street smarts a real world guide to CompTIA security+ skills - Miller, David, 1959 Nov. 5- (Wiley Pub., 2011)
"A step-by-step guide to the tasks involved in security administrationIf you aspire to a career in security administration, one of your greatest challenges will be gaining hands-on experience. This book takes you through the most common security admin tasks step by step, showing you the way around many of the roadblocks you can expect on the job. It offers a variety of scenarios in each phase of the security administrator's job, giving you the confidence of first-hand experience. Security administrators confront a wide assortment of challenging tasks; those seeking a career in security administration are hampered by a lack of actual experience This guide simulates that experience by walking you through a variety of common tasks, demonstrating step by step how to perform them and how to circumvent roadblocks you may encounter Tasks are arranged according to four phases of the security administrator's role: designing a secure network, creating and implementing standard security policies, identifying insecure systems in an existing environment, and training both onsite and remote users This comprehensive workbook provides the next best thing to intensive on-the-job training for security professionals"--